Classe de titular na carreira do magistério do ensino básico, técnico e tecnológico (ebtt): concepções norteadoras para regulamentação, autocuidado, boas práticas e requisitos de acesso - FRANÇA, Jardel (2025)
The titular class in the Teaching Career of Basic, Technical, and Technological Education (EBTT) represents the highest level of functional progression for professors in Federal Institutes. However, its regulation and implementation vary across different institutions, creating challenges for faculty members seeking this promotion. This dissertation aims to investigate the concepts, regulations, and practices related to the titular class in the EBTT career, with a special focus on the Federal Institute of Amapá (IFAP). The research adopts a qualitative and documentary approach, analyzing institutional resolutions and ministerial guidelines to identify best practices and access requirements. Furthermore, the dissertation explores the impact of the titular class on the verticalization of education, considering its influence on the creation of graduate programs and the consolidation of research and extension. The findings indicate that, although general guidelines are established by Law No. 12.772/2012 and MEC Ordinance No. 982/2013, Federal Institutes adopt different criteria and interpretations, making uniform regulation challenging. The study reveals that promotion to the titular class requires not only academic qualifications and service time but also a rigorous evaluation process based on a descriptive memorial or the defense of an unpublished thesis. The research also highlights the importance of functional self-care for faculty members, emphasizing strategies for career planning and adherence to institutional criteria. As an educational product, an introductory didactic guide was developed, providing detailed information on requirements, best practices, and regulations for achieving the titular class. It is concluded that standardization and clarity in regulation are essential to ensure greater equity in access to the titular class, as well as to enhance the academic and professional development of EBTT faculty members.